TORAKOCHIRURGIAThe influence of comorbidity and other risk factors on early postoperative complications after lobectomy for non-small cell lung cancer - Kowalewski, Janusz; Sędłak, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Lobectomy is a preferable operation for I and II stage of non small cell lung cancer. However, this group of patients suffered from great number of comorbidities, which may have influenced postoperative complications. Aim: The aim of the study was to determine the influence of concomitant diseases and other risk factors on development of early complications after lobectomy due to non small cell lung cancer. Material and Methods: The clinical records of 99 patients were analyzed. The risk factors (age, sex, smoking history, BMI, lung cancer staging) and all concomitant diseases were taken into consideration. Any postoperative complications were determined. Univariate and multivariate analysis were employed to define the correlations between risk factors (comorbidities) and postoperative complications. Results: Concomitant diseases were noted in 73% and postoperative complications in 41% of patients. There was no postoperative mortality and rethoracotomy. Using univatiate analysis we proved the correlation between the postoperative air leak and chronic obstructive pulmonary disease (COPD) and coronary disease. Moreover, the correlation between the postoperative fever and diabetes was noted. By multivariate analysis however, it was possible to prove, that tobacco smoking is a significant risk factor for postoperative complications. COPD and patient’s age are strong factors as well, although not significant. Conclusions: Majority of patients operated on for NSCLC suffered from concomitant diseases. Although postoperative complications were noted in 41% of patients, they did not cause death or require rethoracotomy. Smoking is a significant factor predisposing to postoperative complications after lobectomy for NSCLC.